2015
DOI: 10.1016/j.jpain.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Nocebo Hyperalgesia, Partial Reinforcement, and Extinction

Abstract: This study provides novel evidence that partial reinforcement results in weaker nocebo hyperalgesia than continuous reinforcement and that nocebo hyperalgesia fails to extinguish, irrespective of the training schedule. As a result, partial reinforcement may serve as a method for reducing the intensity of nocebo hyperalgesia in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 31 publications
8
75
4
Order By: Relevance
“…The studies differed in the number of trials during conditioning (study 1: 6 CS High and 6 CS Low ; study 2: 12 CS High and 12 CS Low ) and in reinforcement schedules (study 1: 100%; study 2: 75%). These alterations in design were applied to test whether a partial reinforcement schedule, inducing higher uncertainty about US appearance, would result in a higher magnitude of conditioned nocebo responses on a behavioral level in this model of visceral pain. Trial numbers were increased to test for the impact of an extended number of learning trials on nocebo responses as previously suggested in an instructed learning paradigm .…”
Section: Methodsmentioning
confidence: 99%
“…The studies differed in the number of trials during conditioning (study 1: 6 CS High and 6 CS Low ; study 2: 12 CS High and 12 CS Low ) and in reinforcement schedules (study 1: 100%; study 2: 75%). These alterations in design were applied to test whether a partial reinforcement schedule, inducing higher uncertainty about US appearance, would result in a higher magnitude of conditioned nocebo responses on a behavioral level in this model of visceral pain. Trial numbers were increased to test for the impact of an extended number of learning trials on nocebo responses as previously suggested in an instructed learning paradigm .…”
Section: Methodsmentioning
confidence: 99%
“…Another important recent discovery is that both placebo and nocebo effects can be established following partial reinforcement (Au Yeung et al, 2014, Colagiuri et al, in press). Placebo research involving conditioning has almost exclusively involved training with continuous reinforcement, i.e.…”
Section: Learning Mechanismsmentioning
confidence: 99%
“…Partial reinforcement refers to when the cue is paired with the relevant outcome on some, but not all trials (Bouton, 2007). In two recent studies, we compared partial reinforcement with continuous reinforcement for placebo analgesia (Au Yeung et al, 2014) and nocebo hyperalgesia (Colagiuri et al, in press). Partial reinforcement involved pairing activation of a sham electrode with a surreptitious decrease (placebo) or increase (nocebo) in pain during only 62.5% of the training trials and keeping it constant for the remainder.…”
Section: Learning Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is these kinds of expectancies that are generally believed to be the core mechanism of placebo and nocebo effects and that are consequently thought to greatly contribute to the efficacy of active treatments (Kirsch, 1997; Benedetti, 2014; Horing et al, 2014). When placebo or nocebo effects are induced, pain expectations are modified, and these response expectations predict changes in the intensity and unpleasantness of both experimental and clinical pain (Atlas et al, 2012; Schmid et al, 2013; Kirsch et al, 2014; Colagiuri et al, 2015; Peerdeman et al, 2016). Stimulus expectancies may exert an indirect influence on pain experiences, e.g., by affecting behavior, but could possibly also influence pain directly.…”
Section: The Influence Of Different Kinds Of Expectancies On Painmentioning
confidence: 99%